Digital Governance and Public Participation in Emerging Democracies: A Systematic Review - Chege, Amina; Mwakyusa, John; Wanjiru, Esther (Emerging Perspective in Social and Politics, 2026)
Digital governance has emerged as a transformative mechanism for enhancing citizen participation, transparency, and policy responsiveness, particularly in emerging democracies. This systematic review synthesizes existing literature on the role of digital platforms including e-government systems, social media, open data initiatives, and civic technology applications in shaping public engagement and governance outcomes. Using a PRISMA-guided approach, peer-reviewed studies published between 2010 and 2025 were identified from Scopus, Web of Science, and Google Scholar, focusing on emerging or transitional democratic contexts. Thematic analysis was employed to categorize findings across key dimensions: digital governance tools, types of citizen participation, and governance impacts. The review highlights three major global trends. First, the adoption of e-government platforms has streamlined administrative processes, improved public service delivery, and facilitated inter-agency coordination. Second, open government initiatives, including open data platforms and transparency programs, have enhanced accountability and allowed citizens to monitor government performance. Third, civic technology applications, such as participatory budgeting platforms and citizen reporting apps, have fostered more inclusive decision-making and strengthened participatory democracy. Evidence from Southeast Asia, Latin America, and Africa demonstrates that these platforms enable broader political engagement, real-time feedback, and collaborative problem-solving. Despite these advances, challenges remain, including digital inequality, limited institutional capacity, and concerns over data privacy. Addressing these barriers is essential to ensure equitable access and sustainable implementation. The review concludes that digital governance holds significant potential to enhance democratic engagement and policy responsiveness, but its effectiveness depends on comprehensive strategies for inclusive participation, institutional strengthening, and technological integration. Future research should focus on AI integration, comparative cross-country studies, and policies for strengthening digital governance frameworks.